Online marketing for your craft business how to get your handmade products discovered, shared and sold on the Internet - Pullen, Hilary (Newton Abbot David and Charles, 2014)
Witten by an experienced marketing professional working in the crafts market, this book is full of practical tips to improve your online networking skills and save you precious time. It will teach you everything you need to know about online marketing, and how to set measurable goals which will have a positive impact on sales and brand awareness
Includes index
1
Keywords: Handicraft -- Internet marketing; Selling -- Handicraft